Strategic Human Resource for Lean Management involving Quality and Operational Performance - Saiful Bahri, Mohamed; M., Alias; A., Wan Ab Aziz (2014)
The purpose of this study was to investigate the association of strategic human resources for lean management (LM) involving product quality performance and operational performance in Malaysian small and medium size manufacturing industry (SMI). By inference, relationships between strategic human resources management practice, product quality performance and operational performance and associations are analyzed using Pearson‟s correlation, cluster analysis and multiple regression analysis. The findings suggest that strategic human resources practice and implementations has significant associations with product quality performance and operational performance. The results of the study will be of particular interest to practicing production managers or top level managers by learning about the factors stimulating the adoption of strategic human resource for LM.